Knowledge, language use and migration in the town of Huancapón (Cajatambo Lima) - Portilla Durand, Luisa (1999)
The work Conocimiento, uso de lenguas y migración en el centro poblado de Huancapón (Cajatambo, Lima), presented by Luisa Portilla Durand as a thesis for a degree in Linguistics, and consisting of five chapters, is an analysis of the results obtained in the first Sociolinguistic Census carried out in the province of Cajatambo (Dept. of Lima) in 1986. The subject population is that of the town of Huancapón, belonging to the district of the same name, located in the province of Cajatambo.